Cognitive Load and In-Vehicle Human-Machine Interaction - Kun, Andrew L.; Heeman, Peter A.; Paek, Tim; III, W. Thomas Miller; Green, Paul A.; Tashev, Ivan; Froehlich, Peter; Reimer, Bryan; Iqbal, Shamsi; Kern, Dagmar (2011)
Interactions with in-vehicle electronic devices can interfere with the primary task of driving. The concept of cognitive load helps us understand the extent to which these interactions interfere with the driving task and how this interference can be mitigated. The workshop will address cognitive load estimation and management for both driving and interactions with in-vehicle systems, and will also endeavor to provide guidance on problems, goals, hypotheses and approaches for future research in this area.